2019
DOI: 10.1021/acsami.8b22221
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Solid Electrolyte Interface on the Si/C Composite Anode with FEC as the Additive

Abstract: Silicon-based anodes have the potential to be used in next-generation lithium ion batteries owing to their higher lithium storage capacity. However, the large volume change during the charge/discharge process and the repeated formation of a new solid electrolyte interface (SEI) on the re-exposed Si surface should be overcome to achieve a better electrochemical performance. Fluoroethylene carbonate (FEC) has been widely used as an electrolyte additive for Si-based anodes, but the intrinsical mechanism in perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
88
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(90 citation statements)
references
References 43 publications
2
88
0
Order By: Relevance
“…In this work, the specific capacities of all electrodes are calculated based on the mass of Si in the active materials. Due to the fluoroethylene carbonate (FEC) additive in the electrolytes decomposes at 1.24 V,35 cyclic voltammetry (CV) tests of Si NPs, Si/C and C‐SCP electrodes were performed at a scanning rate of 0.1 mV S −1 in a voltage range of 0.01–1.2 V (vs Li/Li + ) for the first 10 cycles. As shown in Figure S10 (Supporting Information), the broad reduction peak at ≈0.67 V of the first cycle is assigned to the formation reaction of solid electrolyte interface (SEI) on Si surface,36 which disappears in the subsequent cycles.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, the specific capacities of all electrodes are calculated based on the mass of Si in the active materials. Due to the fluoroethylene carbonate (FEC) additive in the electrolytes decomposes at 1.24 V,35 cyclic voltammetry (CV) tests of Si NPs, Si/C and C‐SCP electrodes were performed at a scanning rate of 0.1 mV S −1 in a voltage range of 0.01–1.2 V (vs Li/Li + ) for the first 10 cycles. As shown in Figure S10 (Supporting Information), the broad reduction peak at ≈0.67 V of the first cycle is assigned to the formation reaction of solid electrolyte interface (SEI) on Si surface,36 which disappears in the subsequent cycles.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4a exhibits the cyclic voltammetry (CV) curves of Si/C-300 for the initial three cycles. Ab road and weak irreversible peak appeared at approximately 0.98 Vi nt he first cathodic scan, indicating the formationo fa nS EI film caused by the decompositiono fe lectrolyte as wella st he reduction of fluoroethylene carbonate (FEC), whereas the other peaks are associated with the lithiation/delithiationp rocesses in Si and C. [14,38,43] Concurrently,t here is a sharp peak below 0.1 V, which can be assigned to the solidstate amorphization as well as lithiation of Si. [14,26] In the anodic scan, two broad peaks centered at approximately 0.35 Vand 0.53 Vare ascribed to the phaset ransition between amorphous Li x Si and Si.…”
Section: Resultsmentioning
confidence: 99%
“…The capacity loss in the first cycle may be assigned to thei rreversible formation of the stable SEI film, irreversible tappingo fL i + on the surface, and reduction of FEC. [43,45,46] The cycling behavior of Si/C was investigateda tacurrent density of 200 mA g À1 .M eanwhile,R H-Si, which was obtained by calcining Si/C in air,w as also examined under the same conditions to illustrate the effecto fc arbon on the electrochemicalp erformance. Unlike bulk Si and RH-Si, Si/C delivers an enhanced electrochemical performance owing to the small size andc arbon matrix without any further modification or coating process.…”
Section: Resultsmentioning
confidence: 99%
“…Microscopic observation revealed that FEC can form a denser SEI layer than other conventional additives used in Si‐based anodes, which prevents small molecules from penetrating into the Si anode surface. In addition, a large amount of LiF formed can avoid pulverization of Si particles . The ethylene carbonate (EC)‐free FEC‐based electrolyte is found to achieve higher specific capacity and better capacity retention in terms of long‐term cycling .…”
Section: Selection Of Electrolyte For Silicon Anodementioning
confidence: 99%